2021
DOI: 10.1371/journal.pone.0261285
|View full text |Cite
|
Sign up to set email alerts
|

MHANet: A hybrid attention mechanism for retinal diseases classification

Abstract: With the increase of patients with retinopathy, retinopathy recognition has become a research hotspot. In this article, we describe the etiology and symptoms of three kinds of retinal diseases, including drusen(DRUSEN), choroidal neovascularization(CNV) and diabetic macular edema(DME). In addition, we also propose a hybrid attention mechanism to classify and recognize different types of retinopathy images. In particular, the hybrid attention mechanism proposed in this paper includes parallel spatial attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In medical imaging, the ATM can help neural networks focus on key information when processing large amounts of medical image data. As a result, the ATM has been applied to the medical field, including in assisting clinicians with the identification of melanoma [18], retinal lesions [19], the pathological sections of colorectal cancer [20] and breast cancer [21], and it has achieved excellent results. Thus, we believe that adding ATM to our CNN model can effectively improve In short, when the ATM was computing, the input medical image feature was defined as Q(queries), K(keys), and V(values).…”
Section: Methodsmentioning
confidence: 99%
“…In medical imaging, the ATM can help neural networks focus on key information when processing large amounts of medical image data. As a result, the ATM has been applied to the medical field, including in assisting clinicians with the identification of melanoma [18], retinal lesions [19], the pathological sections of colorectal cancer [20] and breast cancer [21], and it has achieved excellent results. Thus, we believe that adding ATM to our CNN model can effectively improve In short, when the ATM was computing, the input medical image feature was defined as Q(queries), K(keys), and V(values).…”
Section: Methodsmentioning
confidence: 99%
“…However, the negative impact of background information on classification results was not analyzed. To concentrate on this aspect, a hybrid attention mechanism was employed in [25], with both spatial and channel attention mechanisms, to minimize the negative impact. Over the last few years, wavelet-based DR detection has been found to have greater influence, and perhaps the Deep Learning models, like CNN's, have progressed in contributing the highest prediction accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…They also compared their model with other methods such as MCME Studies in the classification paradigm explore the integration of attention mechanisms to enhance AMD classification accuracy. Xu et al proposed a hybrid attention mechanism for retinal disease classification using OCT images [16]. Their method, called MHANet, combines parallel spatial and channel attention mechanisms to extract key features of the lesion areas and reduce the influence of background information.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that their method achieved 96.5% and 99.76% classification accuracy on Dataset1 and Dataset2, respectively, outperforming the other recent employed models such as VGG, ResNet, and SENet. They also visualized the attention maps of their method and showed that it can more accurately locate the lesion regions in the images [16]. Li et al have proposed two convolutional neural network (CNN) models to classify four types of age-related macular degeneration (AMD) from retinal images [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation